"Tomorrow belongs to us": the British far right since 1967 - Copsey, Nigel; Worley, Matthew (Routledge studies in fascism and the far right, 2018)
"The men who rewrite history" : Holocaust denial and the British far right from 1967 / Mark Hobbs -- The national socialist group : a case study in the groupuscular right / Daniel Jones and Paul Jackson -- The National Front : the search for a "nationalist" economic policy / John E. Richardson -- Exporting fascism across the commonwealth : the case of the National Front of Australia / Evan Smith -- The dog that didn't bark? : assessing the development of "cumulative extremism" between fascists and anti-fascists in the 1970s / Alex Carter -- White youth : the far right, punk and British youth culture, 1977-87 / Matthew Worley and Nigel Copsey -- Whatever it takes : designing British neo-fascist rock, 1987-2007 / Ana Raposo and Rober Sabin -- The obnoxious mobilised minority : homophobia and homohysteria in the British National Party, 1982-1999 / George J. Severs -- Closing the gender gap : reflections on women's involvement in Britain's contemporary far right / Hannah Bows -- "There's a vital lesson here. let's make sure we learn it" : transnational mobilisation and the impact of Greece's Golden Dawn upon extreme right-wing activism in Britain / Graham Macklin -- Love will tear us apart : emotions, patriotism and the English Defence League / C.M. Quinn -- Britain's far right since 1967 : a bibliographic survey / Craig Fowlie